Media Freedom and Right to Information in Africa - Bussotti, L.; Barros, M.; Gratz, T. (2015)
This e-book is the result of a panel organized in the Fifth European Congress of African Studies (ECAS 5) that took place in Lisbon in June 2013. We thought of organizing this panel on “Press Freedom and Right to Information in Africa” since the question of freedom, especially press freedom, is presently extremely important in all African countries. However, it is not yet well known, both in the academic context and by the public.